Increased Levels of Lectin‐Like Oxidized Low‐Density Lipoprotein Receptor‐1 in Ischemic Stroke and Transient Ischemic Attack. Issue 2 (12th January 2018) - Skarpengland, Tonje; Skjelland, Mona; Kong, Xiang Yi; Skagen, Karolina; Holm, Sverre; Otterdal, Kari; Dahl, Christen P.; Krohg‐Sørensen, Kirsten; Sagen, Ellen L.; Bjerkeli, Vigdis; Aamodt, Anne Hege; Abbas, Azhar; et al.
Abstract : Background: Soluble lectin‐like oxidized low‐density lipoprotein receptor‐1 (sLOX‐1) has been shown to be increased in patients with acute ischemic stroke. Here, we evaluated plasma sLOX‐1 levels and vascular carotid plaque LOX‐1 (ie, OLR1 ) gene expression in patients with ischemic stroke and transient ischemic attack (TIA) with particular focus on their relation to time since symptom onset. Methods and Results: Plasma sLOX‐1 (n=232) and carotid plaque OLR1 gene expression (n=146) were evaluated in patients who were referred to evaluation for carotid endarterectomy, as well as in healthy control plasma (n=81). Patients were categorized according to presence of acute ischemic stroke or transient ischemic attack (n=35) ≤7 days, >7 days ≤3 months (n=90), >3 months (n=40), or no reported symptoms before study inclusion (n=67). Our major findings were the following: (1) Patients with carotid atherosclerosis had increased plasma sLOX‐1 levels as compared with controls. (2) Plaque OLR1 mRNA levels were increased in carotid plaques (n=146) compared with nonatherosclerotic vessels (ie, common iliac arteries of organ donors, n=10). (3) There were no differences in sLOX plasma levels or OLR1 gene expression when analyzed according to the time since relevant cerebral ischemic symptoms. (4) Also patients with severe carotid atherosclerosis without any previous ischemic events had raised sLOX‐1 levels. (5) Immunostaining showed colocalization between LOX‐1 and macrophages within the carotid plaques. (6) Also patients with acute stroke (within 7 days) caused by atrial fibrillation (n=22) had comparable raised sLOX‐1 levels. Conclusions: sLOX‐1 levels are elevated in patients with ischemic stroke and transient ischemic attack independent of cause and time since the ischemic event.